Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Stres Kerja Karyawan PT Plasindo Elok - Febrianti, Dita; Rini, Ratih Setyo (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Workload is one of the most frequently complained causes of stress and is the main reason for employees in an organization. While the work environment is everything around workers that can affect them when carrying out and completing the tasks given. This study consists of three variables, namely workload (X1), work environment (X2) and work stress (Y). This study used a sample of 50 employees of PT Plasindo Elok and used data collection methods through observation, questionnaires with a 5-1 scale and documentation studies. The data analysis method used was SPSS version 25, namely data quality testing, classical assumption testing, multiple linear regression analysis, hypothesis testing and determination coefficient testing (R2). The findings of the study stated that partially workload and work environment have a significant effect on work stress and the resulting regression analysis means that workload and work environment simultaneously have a significant effect on work stress.